An intravenous biological therapy for psoriasis: Infliximab - Mathur, M; Kedia, SK; Chimire, RBK (Journal of College of Medical Sciences-Nepal, 2012)
Psoriasis is a common, chronic inflammatory skin disease which typically follows a relapsing and remitting course and is associated with joint disease. The significant reduction in quality of life and the psychosocial disability suffered by patients underline the need for prompt, effective treatment and long-term disease control. Patients with moderate to severe disease often require systemic treatment with effective & new modalities such as biological-Infliximab. Review will highlight fundamental aspects of infliximab and its use in Psoriasis as well as provide specific comments regarding this monoclonal antibody and its position in of psoriasis in the future treatment. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5977 JCMSN 2011; 7(1): 69-72